2005
DOI: 10.1152/ajpcell.00103.2005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling error and stability of endothelial cytoskeletal membrane parameters based on modeling transendothelial impedance as resistor and capacitor in series

Abstract: . Modeling error and stability of endothelial cytoskeletal membrane parameters based on modeling transendothelial impedance as resistor and capacitor in series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Diabetic PDCs were found to proliferate slightly better than diabetic BMSCs, but underwent even poorer osteogenic differentiation than diabetic BMSCs in normal glucose osteogenic media. Although it was previously shown that restoring normal insulin levels could improve bone quality in T1DM patients [42], early intervention is needed to prevent detrimental “metabolic memory” caused by hyperglycemia [43]. Our observation that skeletal progenitors isolated from T1DM rats with poorly controlled blood glucose exhibit significant cellular impairments in normal glucose cultures supports that restoring normal blood glucose alone may not be sufficient in rescuing skeletal comorbidities of T1DM.…”
Section: Discussionmentioning
confidence: 50%
“…Diabetic PDCs were found to proliferate slightly better than diabetic BMSCs, but underwent even poorer osteogenic differentiation than diabetic BMSCs in normal glucose osteogenic media. Although it was previously shown that restoring normal insulin levels could improve bone quality in T1DM patients [42], early intervention is needed to prevent detrimental “metabolic memory” caused by hyperglycemia [43]. Our observation that skeletal progenitors isolated from T1DM rats with poorly controlled blood glucose exhibit significant cellular impairments in normal glucose cultures supports that restoring normal blood glucose alone may not be sufficient in rescuing skeletal comorbidities of T1DM.…”
Section: Discussionmentioning
confidence: 50%
“…A numerical analysis was used to calculate specific cell-cell and cell-substrate adhesion and C m on the basis of the measured transcellular impedance recorded by the ECIS system using a model described elsewhere (19,22,24) and determined by computer algorithms recently described in complete detail elsewhere (3). Briefly, the total impedance across a cell-covered electrode is composed of the impedance created between the ventral surface of the cell and the electrode (␣), the impedance created between cells (R b), the transcellular impedance created from transcellular current conduction (Zm), and the impedance of a naked electrode (Zn).…”
Section: Materials Humanmentioning
confidence: 99%
“…The computer algorithms resolve measurements of TER into measurements of cell-cell adhesion (R b ), cell-matrix adhesion (␣), and membrane capacitance (C m ). Additionally, these computer algorithms calculate the error of the numerical analysis, which provides an assessment of model stability and reliability (3).…”
mentioning
confidence: 99%
“…These model parameters were then extracted by iteratively least–square–fitting the function to the measured impedance–related RMS output voltages shown in Fig. 1 (Bodmer et al, 2005). A multiple–step–fitting approach was employed in our multi–parameter extraction process in order to minimize the errors (Gordon et al, 1989; Lo et al, 1995).…”
Section: Data Fitting With the Equivalent Circuit Modelmentioning
confidence: 99%